Effectiveness of integrating content and language instruction in an EFL context - Abadikhah, Shirin; Ahangar, Zohreh (Penerbit UKM, 2015)
Integrating content and language instruction has recently become popular in many countries. This approach has gained momentum following the inadequacies observed in comprehension-based classrooms, indicating that the learners were unable to develop native-like proficiency and control over L2 production (Swain, 2001). The present study is an attempt to examine how integrating content and language instruction may affect the accuracy of L2 production in an EFL context. Two groups of learners (n= 36; experimental and control) attended twenty sessions in a semester. In order to examine the participants‟ progress over the term, an achievement test targeting content and linguistic knowledge was administered to both groups during the pretest and posttest sessions. For integration of language into content, the experimental group worked in pairs to complete four focus-on-form tasks (dictogloss) developed on the basis of the content presented to them during the previous sessions. To examine the amount of noticing and progress in the accuracy, their conversations were tape-recorded and transcribed. While performing each task, the learners were asked to write their reconstructed texts in their handouts. The results obtained from the pretest and posttest indicated that the experimental group significantly outperformed the control group in their final scores. It was also revealed that the amount of noticing increased in the experimental group from the first to the fourth task. Furthermore, there was a rising trend in the accuracy of production. The findings lend support to the efficiency of integrating content and language instruction in the Iranian EFL context.